A Novel Aggregation-Induced Emission-Based Electrochemiluminescence Aptamer Sensor Utilizing Red-Emissive Sulfur Quantum Dots for Rapid and Sensitive Malathion Detection - Yajun Wu; Dongxiao Ma; Xiaoli Zhu; Fangquan Xia (Biosensors)
Rapid, effective, and cost-effective methods for large-scale screening of pesticide residues in the environment and agricultural products are important for assessing potential environmental risks and safeguarding human health. Here, we constructed a novel aggregation-induced emission (AIE) electrochemical aptamer (Apt) sensor based on red-emissive sulfur quantum dots (SQDs), which aimed at the rapid screening and quantitative detection of malathion. SQDs were prepared using a two-step oxidation method with good electrochemiluminescence (ECL) optical properties. These SQDs were modified onto the electrode surface to serve as ECL luminophores. Subsequently, Apt was introduced and modified to form a double-helix structure with the complementary chain (cDNA). The ECL signal was reduced because the biomolecules had poor electrical conductivity and inefficient electron transfer. When the target malathion was added, the double helix structure was unraveled, the malathion Apt fell off the electrode surface, and the ECL signal was restored. The linear range of detection was 1.0 × 10−13–1.0 × 10−8 mol·L−1, and the detection limit was 0.219 fM. The successful preparation of the sensor not only develops the ECL optical properties of SQDs but also expands the application of SQDs in ECL sensing.